The art and architecture of Japan - Paine, Robert Treat (Penguin Books, 1975)
Once slighted as mere copying from China, the arts of Japan are now seen as a unique alternation of advances and withdrawals. At times the islanders produced Chinese-style works of great beauty, unmatched on the continent. When they chose to be independent, their art differs at every level. Sculpture, and even more painting, are concrete, sensuous, and emotional, speaking directly to all. All that was most native in architectural taste survived the periods of Chinese monumentality - huge temples and gridiron city plans - with little change. The rambling, wood-paper-and-bamboo dwelling re-emerged 1000 years ago, almost as it may still be seen today.